ANALISIS PENDAPATAN DAN KELAYAKAN USAHA PETERNAKAN AYAM PETELUR HJ. SARI INTAN DI DESA POTOYA KECAMATAN DOLO KABUPATEN SIGI - Aida, Max Nur Alam, Nur (AGROTEKBIS, 2015)
This study aim was to determine income and businessfeasibility of layer chicken poultry Hj Sari Intan in Potoya Village, Dolo Sub District, Sigi District. The study location and respondents were purposively determined. Data collected in this study consisted of primary and secondary information. Data was analyzed using income and feasibility analysis. The study result showed that (1) the income earned was IDR 1,880,725,200 year-1; (2) the value of feasibility obtained was 1,89>1 suggesting that the business is feasible to run.